Two new species of Rhaucus Simon, 1879 reveal putative synapomorphies related to the microstructural morphology of male genitalia (Opiliones: Cosmetidae) - Pinzón-M., Conchita; Pinto-Da-Rocha, Ricardo (Zootaxa, 2024)
Two new species of Rhaucus Simon, 1879 are described from Bolívar, Colombia: Rhaucus gaiterus sp. nov. and Rhaucus artifex sp. nov. Additionally, two species of Meterginus Pickard-Cambridge, 1905 are transferred to the genus Rhaucus based on genital and somatic characters, resulting in two new combinations: Rhaucus serratus (Roewer 1912) comb. nov. and Rhaucus marmoratus (Roewer 1912) comb. nov. Thus, the genus Rhaucus is currently represented by ten species. Structures related to the ventral macrosetae on the ventral plate of the penis are described and proposed as putative synapomorphies, based on the occurrence of these characters in almost all species of this genus. A comparative discussion is provided regarding the morphology of the ozopore in species of this genus. Finally, our findings suggest that Rhaucus is more widely distributed than previously thought, occurring not only in the Andean mountains of Colombia but also in the Ecuadorian Andean mountains and the northern lowlands of Colombia.